Wednesday

April 23, 2014

April 23, 2014

Posted by **C** on Wednesday, July 10, 2013 at 6:23pm.

- Calculus -
**Steve**, Thursday, July 11, 2013 at 10:51amsin(xy)=1+x^3-y^2

cos(xy) (y + xy') = 3x^2 - 2yy'

y cos(xy) + xcos(xy) y' = 3x^2 - 2yy'

(x cos(xy) + 2y) y' = 3x^2 - y cos(xy)

y' = (3x^2 - y cos(xy)) / (x cos(xy) + 2y)

**Related Questions**

Calculus - I am unsure of how to take the derivative of this equation. It may be...

Calculus - Use implicit differentiation to find dy/dx if cos xy = 2x^2 - 3y. I'm...

Calculus (repost) - Use implicit differentiation to find dy/dx if cos xy = 2x^2...

calc - 1 + x = sin(xy^2) find dy/dx by implicit differentiation 0 + 1 = cos(xy^2...

calculus - a particle moves along the curve xy=10. if x=2 and dy/dt=3, what is ...

Math, Calculus - help Please... Differential Equations Problems... please give ...

Mathematics - Solve the following differential equation, i.e. solve for y: dy/dx...

Match, Calculus - help Please... Differential Equations Problems... please give ...

Calculus - How do you us implicit differentiation to solve x( y + 2 )^5 = 8 x( y...

math calculus - Hi could someone please explain to me how i would use the chain ...